Library Video Tutorials to Support Large Undergraduate Labs: Will They Watch? - April L. Colosimo; Emily Kasuto (Issues in Science and Technology Librarianship, 2012)
Video tutorials were designed for students working on a General Chemistry scientific inquiry laboratory in 2008, as a supplement to in-class instruction from a librarian. In 2010, with no opportunity to provide in-class instruction, one of the videos was redesigned and offered to assist students with the exercise. In both years, students were asked to provide feedback on the usefulness of the videos and their willingness to watch library tutorials in general. This study compares feedback from 2008 (533 respondents) to 2010 (850 respondents). The changes in circumstances had little effect on student attitudes towards this mode of teaching. [ABSTRACT FROM AUTHOR.]